The Pilgrim of Castile; or, El Pelegrino in Su Patria - Vega, Lope de, 1562-1635; Dutton, William (Salt Lake City, UT : Project Gutenberg, 2015)
"The Pilgrim of Castile; or, El Pelegrino in Su Patria" by Lope de Vega is a historical romantic novel written in the early 17th century. The story revolves around a shipwrecked pilgrim who washes ashore near Barcelona, ultimately leading to a tale filled with love, betrayal, and the quest for honor as various characters intertwine amidst perilous adventures. The protagonist, initially shrouded in mystery and facing numerous obstacles, engages in the grand themes of longing and redemption. At the start of the narrative, the protagonist is rescued by fishermen after being thrown ashore from a wrecked ship. Upon coming back to consciousness, he recounts his harrowing tale, revealing his background and the cause of his journey to Italy for the Jubilee. As the story unfolds, he encounters soldiers and hears tragic stories of love, betrayal, and revenge involving characters like Doricles, Filander, and Florinda, which sets the stage for conflicts driven by love and nobility. The tale intricately weaves various narratives together, reflecting on the cost of desires and the toll of inner turmoil amidst the quest for honor and recognition. (This is an automatically generated summary.)
Abridged.
Release date is 2015-09-01
Produced by Nigel Britton
Keywords: Spanish fiction -- Translations into English